INCLUSIVE EDUCATION DESIGN AT 263 RANCALOA STATE ELEMENTARY SCHOOL, BANDUNG CITY - Ineu Sumarsih; Ishmahani Sobarningsih; Teni Marliyani (Jurnal Scientia, 2022)
The introduction of inclusive education at SDN 263 Rancaloa can be equated with providing opportunities for children with special needs in Rancasari District to exercise their legal rights. In accordance with the level of specialization, students with special needs can complete the school curriculum and achieve final results at the lower secondary level. This study uses the literature study methodology. The purpose of this article review is to find out the educational management plan related to inclusion at SDN 263 Rancaloa. Planning, organizing, practicing and monitoring curricula and teaching standards are some of these tasks. This study uses the method of literature review. In-depth interviews with several key informants were conducted as part of the data collection process, and the information was then categorized according to the topic of study. The level of data validity is maintained through the use of triangulation and member check mechanisms. The findings of this study help explain how inclusive education is managed. Namely as follows: (1) inclusive education planning includes curriculum and teaching quality; (2) organizing is done by selecting inclusive education coordinators, inclusive class teachers, and subject teachers for inclusive classes; (3) debriefing is done with leadership, communication, and motivation; and (4) control is carried out once every three months. (1) inclusive education planning includes curriculum and teaching quality; (2) organizing is done by selecting inclusive education coordinators, inclusive class teachers, and subject teachers for inclusive classes; (3) debriefing is done with leadership, communication, and motivation; and (4) control is carried out once every three months. (1) inclusive education planning includes curriculum and teaching quality; (2) organizing is done by selecting inclusive education coordinators, inclusive class teachers, and subject teachers for inclusive classes; (3) debriefing is done with leadership, communication, and motivation; and (4) control is carried out once every three months.